2018
DOI: 10.1016/j.jaci.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Low-level ozone has both respiratory and systemic effects in African American adolescents with asthma despite asthma controller therapy

Abstract: Capsule Summary: In a cohort of African American adolescents with persistent asthma on guidelines-based daily controller therapies, short–term elevation of low ozone levels below the National Ambient Air Quality Standard of 70 ppb were associated with lung function decrements and elevated lipid levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…Interestingly, we identified that no usage of an indoor air purifier during exposure to high levels of outdoor air pollution was associated with moderate/severe asthma when mild intermittent asthma was considered as a reference. Air pollution is known to affect respiratory health, including asthma, with increases in hospitalization 30. In a previous study, the use of high-efficiency particulate air (HEPA) filters decreased the frequency of unscheduled clinic visits due to asthma exacerbation in children 31.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, we identified that no usage of an indoor air purifier during exposure to high levels of outdoor air pollution was associated with moderate/severe asthma when mild intermittent asthma was considered as a reference. Air pollution is known to affect respiratory health, including asthma, with increases in hospitalization 30. In a previous study, the use of high-efficiency particulate air (HEPA) filters decreased the frequency of unscheduled clinic visits due to asthma exacerbation in children 31.…”
Section: Discussionmentioning
confidence: 98%
“… 99 , 100 Also in the lower airways, short-term natural increase in ambient air ozone was associated with deteriorating lungh function tests in atopic asthmatics despite use of proper asthma controller therapy. 101 Similarly, an ozone exposure protocol revealed atopic asthmatics expressed depressed spirometry testing results compared to healthy volunteers. 102 Along with this, climate chamber studies revealed (ozone) exposure of healthy or allergic asthmatics induces a neutrophilic 103 or a mixed neutrophilic and eosinophilic 104 inflammatory profile in the lower airways, respectively.…”
Section: Comparative Analysis Of Oxidative Stress-mediated Immunopathmentioning
confidence: 98%
“…Children who live near major roadways and exposed to traffic-related air pollution have increased susceptibility to asthma. A recent study has shown that exposure to air ozone levels at sub-NAAQS thresholds is associated with pulmonary and systemic changes in African American adolescents with asthma [64]. In general, the burden of air pollution related asthma is associated with a lower socioeconomic status, and is thus a health equity issue [65].…”
Section: Air Pollutionmentioning
confidence: 99%